2005
DOI: 10.3748/wjg.v11.i41.6557
|View full text |Cite
|
Sign up to set email alerts
|

Left paraduodenal hernia presenting as recurrent small bowel obstruction

Abstract: Internal herniation of the small bowel is a relatively rare cause of intestinal obstruction. Left paraduodenal hernia resulting from abnormal rotation of the midgut during embryonic development is the most common form of congenital internal hernia. We report our experience in the diagnosis and management of a young male with left paraduodenal hernia presenting as recurrent intestinal obstruction. Correct preoperative diagnosis of left paraduodenal hernia had been difficult due to non-specific clinical presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 6 publications
1
55
0
1
Order By: Relevance
“…They may sometimes be asymptomatic and can be incidentally identified by imaging studies performed for other reasons, during laparotomy or autopsy series (2,6,9,10). Clinical symptoms are in the form of recurrent cramp-like abdominal pain, intestinal obstruction due to torsion, nausea, vomiting and abdominal distention (3,5). Tong et al (9) evaluated 32 cases, and they reported that chronic symptoms are seen in 69% of patients and that 66% of patients present with acute obstruction or strangulation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They may sometimes be asymptomatic and can be incidentally identified by imaging studies performed for other reasons, during laparotomy or autopsy series (2,6,9,10). Clinical symptoms are in the form of recurrent cramp-like abdominal pain, intestinal obstruction due to torsion, nausea, vomiting and abdominal distention (3,5). Tong et al (9) evaluated 32 cases, and they reported that chronic symptoms are seen in 69% of patients and that 66% of patients present with acute obstruction or strangulation.…”
Section: Discussionmentioning
confidence: 99%
“…Paraduodenal hernia is observed 3 times more in the left than in the right (3, 5-7, 9, 10). It is most commonly seen in the 4th and 6th decades (3,5). Its occurrence in men is three times more common than in women (3,5,6,9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations